Aortic Counterpulsation Therapy in Patients with Advanced Heart Failure: Analysis of the TBRIDGE Registry - Bezerra,Cristiano Guedes (2016)
Abstract Background: The use of aortic counterpulsation therapy in advanced heart failure is controversial. Objectives: To evaluate the hemodynamic and metabolic effects of intra-aortic balloon pump (IABP) and its impact on 30-day mortality in patients with heart failure. Methods: Historical prospective, unicentric study to evaluate all patients treated with IABP betwen August/2008 and July/2013, included in an institutional registry named TBRIDGE (The Brazilian Registry of Intra-aortic balloon pump in Decompensated heart failure - Global Evaluation). We analyzed changes in oxygen central venous saturation (ScvO2), arterial lactate, and use of vasoactive drugs at 48 hours after IABP insertion. The 30-day mortality was estimated by the Kaplan-Meier method and diferences in subgroups were evaluated by the Log-rank test. Results: A total of 223 patients (mean age 49 ± 14 years) were included. Mean left ventricle ejection fraction was 24 ± 10%, and 30% of patients had Chagas disease. Compared with pre-IABP insertion, we observed an increase in ScvO2 (50.5% vs. 65.5%, p < 0.001) and use of nitroprusside (33.6% vs. 47.5%, p < 0.001), and a decrease in lactate levels (31.4 vs. 16.7 mg/dL, p < 0.001) and use of vasopressors (36.3% vs. 25.6%, p = 0.003) after IABP insertion. Thirty-day survival was 69%, with lower mortality in Chagas disease patients compared without the disease (p = 0.008). Conclusion: After 48 hours of use, IABP promoted changes in the use of vasoactive drugs, improved tissue perfusion. Chagas etiology was associated with lower 30-day mortality. Aortic counterpulsation therapy is an effective method of circulatory support for patients waiting for heart transplantation.